A framework for multi-objective facility layout design. (December 2015) - Saraswat, Ashish; Venkatadri, Uday; Castillo, Ignacio
Highlights: Multi-objective meta-heuristic framework for the BLP. Integrating several recent advances in the layout design. More than one possible layout to implement depending on management preferences. Good starting point when faced with a decision about which layout to implement. Abstract: The most commonly used metric for facility layout design in the academic literature is the flow–distance metric, a weighted average between the material transfer and the distance travelled. Researchers and practitioners, however, have recognized that other metrics are also important. Facility layout designs obtained using the flow–distance metric exclusively have been criticized because they completely ignore empty material transfer, which generally increases work-in-process and equipment costs. Therefore, facility layout design (block layout design in particular) based exclusively on the flow–distance metric is insufficient. In this paper, we present a framework that utilizes the recent advancements in the facility planning literature to generate block layout designs based on three objectives: flow–distance, average work-in-process, and the number of required material handling devices. Numerical experiments are conducted on a number of standard problems, and the tradeoffs between the different objectives are studied. Our study indicates that it is critical to pursue multi-objective analysis and optimization for the actual implementation of the layouts.